Toward Improved Description of DNA Backbone: Revisiting Epsilon and Zeta Torsion Force Field Parameters - Zgarbová, Marie (2013)
We present a refinement of the backbone torsion parameters ε and ζ of the Cornell et al. AMBER force field for DNA simulations. The new parameters, denoted as εζ(OL1), were derived from quantum-mechanical calculations with inclusion of conformation-dependent solvation effects according to the recently reported methodology (J. Chem. Theory Comput. 2012, 7(9), 2886-2902). The performance of the refined parameters was analyzed by means of extended molecular dynamics (MD) simulations for several representative systems. The results showed that the εζ(OL1) refinement improves the backbone description of B-DNA double helices and G-DNA stem. In B-DNA simulations, we observed an average increase of the helical twist and narrowing of the major groove, thus achieving better agreement with X-ray and solution NMR data. The balance between populations of BI and BII backbone substates was shifted towards the BII state, in better agreement with ensemble-refined solution experimental results. Furthermore, the refined parameters decreased the backbone RMS deviations in B-DNA MD simulations. In the antiparallel guanine quadruplex (G-DNA) the εζ(OL1) modification improved the description of non-canonical α/γ backbone substates, which were shown to be coupled to the ε/ζ torsion potential. Thus, the refinement is suggested as a possible alternative to the current ε/ζ torsion potential, which may enable more accurate modeling of nucleic acids. However, long-term testing is recommended before its routine application in DNA simulations.